An 18F-MD-PSMA (Multi-dentate PMSA Imaging Agent) PET/CT in Prostate Cancer Relapse: Results of a Retrospective Trial - Fu, Hongliang; Liang, Sheng; Xu, Miaomiao; Guo, Jun; Liu, Qiang; Kang, Jian; Zhang, Linlin; Liu, Zihao; Ding, Lin; Ma, Yufei; Yang, Bin; Yao, Xudong; et al. (Current Radiopharmaceuticals, 2024)
Purpose: This study aimed to evaluate the performance of 18F-MD-PSMA PET/CT in patients previously treated for prostate cancer by either surgery or therapy, but later relapsed biochemically. Methods: This retrospective study enrolled 213 patients in sequence previously treated for prostate cancer by either surgery or therapy, but later PSA relapsed. A total of 191 of these 213 patients were included in this analysis. All patients were biochemically relapsed after radical prostatectomy or therapy, had 18F-MD-PSMA PET/CT scan within 1 week, and were off hormonal therapy at the time of the scans. The new tracer was compared directly with 11C-choline in sensitivity. Results: In 3 patients, a side-by-side comparison between 18F-MD-PSMA and 11C-choline was performed, and it was found that the former was about 3 times more sensitive than the latter. The analysis of PET imaging using 18F-MD-PSMA in 191 relapsed patients showed that less than 10% of patients showed the disease limited in the prostate. Among the remote lesions, the number in decreasing order was bone, followed by lymph nodes and other organs. The maximal SUV in lesions in each patient followed an exponential decay, with SUV inclined to the lower end. The Gleason score measured at the diagnosis showed no correlation with the average number of lesions in each patient, the average maximal SUV values among this cohort of patients, and the PSA values measured at the time of PET imaging. The number of lesions observed in each patient has no correlation with the PSA value measured at the time of PET imaging. When PSA value was measured as an independent biomarker at the time of PET imaging, the positivity of PET imaging using 18F-MD-PSMA increased along with an increase in PSA value, but with exceptions where PSMA expression was low or negative. From the PET imaging of this radioligand, the majority of patients showed oligo-metastasis, favoring using local therapy to manage the disease. Conclusion: An 18F-MD-PSMA as a radioligand was found to be superior to 11C-choline in the setting of patients with biochemical relapse after previous treatment. Its PET imaging results matched those of established PSMA radioligands, but its chemical structure was found to have added features to conjugate with other functional molecules, such as those with therapeutic properties. This radioligand lays the foundation for our further work.
Keywords: oligo-metastasis